Spotlight ? Minerals & Materials ?96 - F. W. Petersen (The Southern African Institute of Mining and Metallurgy, 1996)
The Conference Minerals & Materials '96 was held in Somerset West, South Africa, from 31st July to 2nd August, 1996. It was organized by the Universities of Stellenbosch and Cape Town, the Cape Technikon, and the Western Cape Branch of The South African institute of Mining and Metallurgy (SAIMM). The three-day Conference was attended by 180 delegates, representing countries such as Australia, South Africa, United Kingdom, Finland, Sweden, Germany, Poland, Zambia, and Zimbabwe. The programme and associated exhibition were well organized, and each of the delegates received two volumes of proceedings containing the 77 papers presented at the Conference.